?ESSENTIAL ELEMENTS IN DIFFERENT PARTS OF KASNI (CICHORIUMINTYBUS): ?Short Communication (Biological Sciences - PJSIR, 2000)
Eight essential elements (Co, Cr, Cu, Fe, Mg, Mn, Ni and Zn) in different parts of Cichorium intybus were analysed by atomic absorption spectrophotometry. The results indicated that the plant contains sufficient amount of nutritional elements.